The evolving global plastics policy landscape: An inventory and effectiveness review. Issue 134 (August 2022) - Diana, Zoie; Vegh, Tibor; Karasik, Rachel; Bering, Janet; D. Llano Caldas, Juan; Pickle, Amy; Rittschof, Daniel; Lau, Winnie; Virdin, John
Abstract: Governments worldwide are increasingly adopting public policies, laws, and ordinances to reduce plastic pollution. To date, studies have not analyzed the content of, and trends in, these policies. Employing a content analysis and literature search, we set out to better understand: (i) governments responses to this problem over time, and (ii) the state of the available evidence on the effectiveness of policy responses. Our motivations were to: (i) expand evidence-based policy-making to reduce plastic pollution by identifying and classifying the policy instruments used by governments; (ii) compile evidence regarding policy effectiveness; and (iii) provide a global database in the form of a Plastics Policy Inventory (https://nicholasinstitute.duke.edu/plastics-policy-inventory ) to track government responses, as requested by the United Nations Environment Assembly in Resolution 4/6. Policies that fell within our scope aimed to reduce plastic pollution beyond business-as-usual solid waste management schema. This Inventory and study have an English-language bias. International and national policies are fairly representative of plastic pollution policies and the subnational ( e.g., states, cities) policies are examples. International governments most frequently used plans and commitments for future action. National and subnational governments most frequently used bans. Ten policies targeted only microplastics and one policy targeted tire wear particles, lagging reported pollution. The peer-reviewed literature reported plastic bag consumption reductions between 27% and 100% after policy adoption. This work lays a foundation for future evidence-based policymaking to reduce plastic pollution and provides a useful tool to track policies, analyze existing policies from new angles, and target gaps in the global plastics policy landscape. Highlights: 291 plastic pollution policies were compiled in a free, open-access inventory. National and subnational policies most frequently banned macroplastics and bags. International policies most frequently featured plans for future action. Plastic bag policies were most commonly studied for effectiveness. Policies on every level infrequently targeted microplastics or tire wear particles.